Structure and dynamics of the supercluster of galaxies SC0028-0005 - O'Mill, Ana Laura (2015)
According to the standard cosmological scenario, superclusters are objects that have just passed the turn-around point and are collapsing. The dynamics of very few superclusters have been analysed up to now. In this paper, we study the supercluster SC0028-0005, at redshift 0.22, identify the most prominent groups and/or clusters that make up the supercluster, and investigate the dynamic state of this structure. For the membership identification, we have used photometric and spectroscopic data from Sloan Digital Sky Survey Data Release 10, finding sixmain structures in a flat spatial distribution. We have also used a deep multiband observation with MegaCam/Canada-France-Hawaii Telescope to estimate de mass distribution through the weak-lensing effect. For the dynamical analysis, we have determined the relative distances along the line of sight within the supercluster using the Fundamental Plane of early-type galaxies. Finally, we have computed the peculiar velocities of each of the main structures. The 3D distribution suggests that SC0028-005 is indeed a collapsing supercluster, supporting the formation scenario of these structures. Using the spherical collapse model, we estimate that the mass within r = 10 Mpc should lie between 4 and 16 × 1015M ⊙. The farthest detected members of the supercluster suggest that within ~60 Mpc the density contrast is δ ~ 3 with respect to the critical density at z = 0.22, implying a total mass of ~4.6-16 × 1017M ⊙, most of which in the form of low-mass galaxy groups or smaller substructures.